Deep Learning for Classification of Sleep EEG Data during the Epidemic of Coronavirus Disease (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: Sleep EEG; deep learning; softmax function; adam algorithm; multiple classifications problem